2022
DOI: 10.3390/ani12192627
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Multilocus Sequence Typing, Virulence Genes and Drug Resistance of Klebsiella pneumoniae Isolated from Cattle in Northern Jiangsu, China

Abstract: Klebsiella pneumoniae (K. pneumoniae) induced bovine mastitis has been becoming one of the dominantly pathogenic bacteria in cases of bovine mastitis, and is threatening public health through dairy products. In order to explore the characteristics of multilocus sequence typing (MLST), virulence gene carrying, and the relationship between virulence genes and the antibiotic resistance of Klebsiella pneumoniae from dairy cattle in northern Jiangsu, 208 dairy milk samples were collected from four dairy farms in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 38 publications
9
10
0
Order By: Relevance
“…COL is a last resort antibiotic to treat infections caused by K. pneumoniae , and the resistance rate to this antibiotic has increased in recent years from 4.8% in 2013–2018 to 8.2% in 2019–2021 [ 35 ]; our resistance rate still higher, when compared to this finding and might come from the transmission between strains as this antimicrobial, was used for treatment calves with diarrhea. CIP, ENR, PIP, IMI, and STX were highly sensitive in our study, which could be a good choice for mastitis treatment, especially CIP, PIP, and IMI, as these drugs had never been used before at studied farms; this finding was supported by other studies in Brazil [ 6 ], in China [ 31 ]. We found that all isolates were sensitive to GEN and EFT; these drugs also be a good option for veterinarians to deal with mastitis cows.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…COL is a last resort antibiotic to treat infections caused by K. pneumoniae , and the resistance rate to this antibiotic has increased in recent years from 4.8% in 2013–2018 to 8.2% in 2019–2021 [ 35 ]; our resistance rate still higher, when compared to this finding and might come from the transmission between strains as this antimicrobial, was used for treatment calves with diarrhea. CIP, ENR, PIP, IMI, and STX were highly sensitive in our study, which could be a good choice for mastitis treatment, especially CIP, PIP, and IMI, as these drugs had never been used before at studied farms; this finding was supported by other studies in Brazil [ 6 ], in China [ 31 ]. We found that all isolates were sensitive to GEN and EFT; these drugs also be a good option for veterinarians to deal with mastitis cows.…”
Section: Discussionsupporting
confidence: 88%
“…Resistance to AMP was supported by similar studies in China [ 28 ] with 100% resistance, in Pakistan with 98% resistance to LIN, 86% AMP, and 99% SUX to mastitis pathogens [ 29 ]. Resistance toward AMP was used to predict the resistance to AMO [ 30 ]; thus, our AMO resistance was found to be high (56%) together with AMP, especially when compared with similar findings in China with 23.5% [ 31 ]. These drugs have been widely used in farms for a long time to deal with clinical mastitis, which may be why resistance to these antimicrobials is high.…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, our data indicated that major virulence traits of the recovered Klebsiella spp were fimA (90%), aerobactin (85%), rmpA (90%) and magA (80%) (Figure 1). Similar findings of fimA, rmpA, and aerobactin genes were also detected in previous studies (Xu et al, 2022). It is documented that the most common virulence factors of Klebsiella spp.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 89%
“…K lebsiella organisms are opportunistic nosocomial pathogens primarily associated with variety of infectious diseases including upper respiratory tract infections especially pneumonia, also, mastitis, blood stream infections and pyogenic liver abscesses in animals and mammals (Butaye et al, 2021;Xu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation